Comparative evaluation of flexible nasopharyngolaryngoscope (FNPLS) with laryngeal ultrasound for assessment of pediatric dysphonia - Muhammad, Athierah; Mohd Nor, Khadijah; Azwal, Norazwani; Abu Hassan, Hasyma; Abu Bakar, Saraiza (2024)
This study assesses the diagnostic accuracy of ultrasound compared to laryngoscopy in identifying laryngeal disorders, such as laryngomalacia, valleculae cysts, vocal cord nodules, and vocal cord paralysis. The sensitivity and specificity of ultrasound were calculated for each condition, highlighting its potential as a diagnostic tool. While results showed high accuracy for most conditions, limitations were noted in detecting vocal cord paralysis.